Zinc batteries : basics, developments, and applications - Boddula, Rajender; Inamuddin, 1980-; Asiri, Abdullah M. (John Wiley & Sons, Inc. ; Scrivener Publishing LLC, 2020)
"Battery technology is constantly changing, especially as more and more industries are choosing to "go green" with newer and cleaner sources of energy. Books like this keep engineers and students abreast of the latest developments in this important area, as well as acting as a refresher for veteran engineers or an introductory text for students"--